Pengaruh Kualitas Pelayanan Dan Penanganan Komplain Terhadap Loyalitas Pelanggan PT. First Media Di Sidoarjo (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS DR SOETOMO SURABAYA, 2022)
The purpose of this study was to analyze the effect of service quality and complaint handling on customer loyalty. The research was conducted using causal quantitative research methods. Causal research is used to prove the relationship between cause and effect of several variables. Data analysis used multiple linear analysis, and used statistical tests of T-test and F-test for hypothesis testing. The results show that service quality has a partial effect on customer loyalty and complaint handling does not partially affect customer loyalty. Simultaneous test results show that service quality and complaint handling have a joint influence on customer loyalty, while the dominant test cannot be tested because one of the research variables has no effect on customer loyalty variables.